THE USE OF IMPLICATURES IN UZBEK NOVELS AND APPROACHES OF TRANSLATING THEM INTO ENGLISH - Firuzabonu Bekmurodova (EPRA International Journal of Research and Development (IJRD), 2023)
This article explores the challenges of understanding linguistic meaning, particularly the study of conversational implicatures in pragmatics. It emphasizes Paul Herbert Grice’s theory of Conversational Implicatures, which involves the Cooperative Principle and the Maxims of Conversation, and how it relates to translation procedures. Moreover, analysis was based on Uzbek novels involving cultural references.